NFC technology improving depressive symptoms in adolescents with depression: quasi-experimental study - Susaree Prakhinkit; Adjara Titawattanaku (International Journal of Public Health Science (IJPHS), 2026)
Depression is a critical global mental health problem that occurs frequently in adolescent in Thailand and can lead to severe consequences, including suicide. Near field communication (NFC) provides a new way for accessing user to data of mental health care. The objectives this study was to determine the effects of NFC on depressive symptoms. A quasi-experimental two-group pretest-posttest was designed. The provincial school was randomly allocated to the control group CON, NFC groups. Each group consisted 50 participants aged 16-18 years who had depression scores 22 on the Center for Epidemiological Studies-Depression Scale (CES-D). The NFC group used NFC-enabled smartphones and NFC tags for four weeks in their home environment. The first paticipants were assigned developing self awareness, the second were assigned emotional expression, third were assigned coping strategies, the finally the participants were recieved reflection activity, and SC group received standard care and followed their normal daily routines. After completing intervention, participans responded CES-D. The results indicated that depressive symptoms in the NFC group significantly decreased post-intervention compared to the baseline p < .05. Furthermore, the NFC group demonstrated significantly lower depression scores than the control group after completing the program p < .05. In conclusion, NFC technology is an effective decreasing depressive symptom in adolescents with depression.